EIB Investment Report 2023/2024 - Key Findings - European Investment Bank (European Investment Bank, 2024)
The European economy is under pressure. Growth is slowing and competitive challenges are rising, all while EU firms navigate the demands of the green transition. Coordinated support from national governments and EU institutions proved critical after the COVID-19 pandemic, helping Europe to bolster its resilience to future shocks and spurring the investment needed to transform and modernise the economy. As a result, progress was made in digitalisation, energy efficiency, decarbonisation and reinforcing supply chains.The pace of change needs to accelerate, however, even as investment becomes harder to sustain. To remain competitive, the European Union and its members need to improve productivity, encourage innovation, address skill gaps, develop new technologies and supporting young, dynamic firms. The report, which is based on the EIB Group’s annual Investment Survey, provides insights on how EU firms are dealing with these pressures, and whether they are taking the necessary steps to transform their businesses.These key findings, provide a short accessible summary of the main report’s messages.